2018
DOI: 10.3390/su10103674
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Aspects Regarding LED Lighting Retrofit—from Case Studies to Vision

Abstract: The lighting industry is still a linear economy, despite the extensive use of light-emitting diode (LED) and the ban of incandescent/halogen lamps, claiming to be greener and more human centered. Light-emitting diode has changed radically the whole lighting industry with an increased luminaire efficacy more than four times higher compared with fluorescent lamps and their new opportunities for modern control systems. In the years to come, millions of fluorescent luminaires will become waste and will be replaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The classical linear economy is based on the manufacture of short-lived products, planned obsolescence, economies of scale, and the consequent growing consumer demand for new products. While the CE is based on the consideration of the negative externalities that the consumption of resources originates [9]. Therefore, CE is focused on how to avoid, minimize, restore, and/or compensate stakeholders [39,40].…”
Section: The Conceptualization Of Circular Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical linear economy is based on the manufacture of short-lived products, planned obsolescence, economies of scale, and the consequent growing consumer demand for new products. While the CE is based on the consideration of the negative externalities that the consumption of resources originates [9]. Therefore, CE is focused on how to avoid, minimize, restore, and/or compensate stakeholders [39,40].…”
Section: The Conceptualization Of Circular Supply Chainmentioning
confidence: 99%
“…However, the application of the principles of the circular economy to the functioning of the supply chain, requires organizations to redesign their chains under a new approach [8]. The circular economy (CE) is an alternative paradigm to the current and dominant production model called "take-make-waste-dispose" [9][10][11][12] that causes a high amount of waste and an inability to regenerate the resources used. Therefore, CE can be considered an attempt to respond to a productive system based on the incessant development of economies of scale that will enable a continuous and growing demand for new products and services to be satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…Even more importantly, our focus on light pollution misses a number of crucial questions related to the sustainability of LED lifecycles. These questions concern the exploitation and recycling of raw materials and the sustainability of value and production chains [72][73][74].…”
Section: Conclusion: the Dilemma Behind The Led Paradoxmentioning
confidence: 99%
“…Using the university adopted lighting retrofit solutions as case studies, circular economy aspects were identified [13]. For a LED retrofitted recessed luminaire T8 4 × 18 W, a previous study [14], showed a major reduction of installed power as well as a correct lighting distribution, but also revealed some issues: lack of certification of the retrofit luminaire, the necessity of utilizing qualified personnel, high workforce costs, etc. Based on the global International Energy Agency (IEA) data, the lighting electricity consumption of commercial buildings in 2005 [12] was about 25 kWh/sq.…”
Section: Introductionmentioning
confidence: 99%